Effect of Leadership Style on Policy Timeliness and Performance of Smart City in Dubai: A Review - Shwedeh, Fanar; Hami, Norsiah; Abu Bakar, Siti Zakiah (2020)
This study conceptually reviews the role of leadership style on the relationship between smart city policy timeliness (that is, smart city policy formulation, implementation and evaluation) and smart city performance. To achieve this, the scholars reviewed earlier literatures, as well as government portals on the development of smart city agenda in Dubai while relating it to earlier smart cities. The findings reveal that the leadership style used in Dubai ‘transformational leadership’ would enhance the smart city policy stages. Considering this, the scholars conclude that the transformational leadership style is an important factor that speeds up the smart city policy stages in implementing smart city agenda